Mechanisms of action of intestinal microorganisms and advances in head and neck tumors - Su Xialu; Ma Faqiang (Discover Oncology)
Abstract In the last decade, it has been discovered that intestinal flora can affect various organ-specific cancers by altering the body's energy balance, synthesizing genetic toxins and small signaling molecules, and initiating and modulating immune responses. In this review, we will focus on elucidating the role of intestinal flora based on its molecular mechanisms and its possible impact on head and neck cancers in the near future, and explore how it may be a novel approach to treating head and neck cancers in the future.